Middle World - Haw, M. author. aut Link
V, 202 p.
Keywords: Between the microscopic world of quarks and atoms, and the macroscopic (observable) one of pebbles and planets, there is another world, strangely neglected by science. It is inhabited by things like pollen, DNA and viruses. Physicist Mark Haw tells the story of how scientists finally saw the restless middle world, having ignored it for so long.